Development of an E-Comic Learning Media on the Human Digestive System to Improve Learning Outcomes - Mufti Setya Rahayu; Aldina Eka Andriani (JURNAL PENDIDIKAN MIPA, 2026)
The limited use of learning media technology based that use storytelling has resulted in low learning outcomes among class V regarding the human digestive system. This project aims to describe the design and development, test the feasibility, and evaluate the effectiveness of an E-Comic learning media on the human digestive system to improve learning outcomes. This is an R&D study using model ADDIE, which includes the stages of analyze, design, development, implementation, and evaluation. The subjects research is 27 class V students. Techniques data collection used non-test methods, including observation, interviews, documentation, and questionnaires, as well as test methods consisting of pre-test and post-test. Data analysis techniques used normality tests, paired sample t-tests, and N-Gain tests. The e-comic design was developed using canva for design, supplemented with stimulation, educational video, and educational games. The feasibility of the e-comic was demonstrated by expert validation results: 90% from content experts and 97.73% from media experts, both categorized as “highly worthy,” supported by teacher feedback of 97.73% and student feedback of 90.54%. The effectiveness of the e-comic was demonstrated by a 20.07% increase in learning outcomes. This was supported by the results of the paired-sample t-test, which showed a significance value of 0.000 < 0.05, and an N-Gain of 0.74, classified as high. The research concluded that the E-Comic learning media was developed successfully, is feasible, and is effective in improved learning outcomes for the human digestive system material for class V students at SD Negeri Karangayu 02 Semarang City.